Bayer recognizes the relevancy of their role in in Food Loss and Waste (FLW) and trade-offs on Climate Action, affecting/motivating Bayer’s company strategy and roadmap in this field - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
In a series of workshops by the WUR CCAFS project team with Bayer key officials and staff around the globe, hotspots on FLW in food supply chains and link with GHG emissions were discussed, substantiated by dedicated analysis of Bayer solutions the Agro-Chain greenhouse gas Emissions (ACE) calculator. Consequently Bayer has decided to take action by selecting priority countries and crop (like rice in India), aiming for partnering (first mover local/regional projects) with involvement of other global players to develop chain-integrative solutions.